Intuitive physics ability in systemizers relies on differential use of the internalizing system and long-term spatial representations - Riekki Tapani; Salmi Juha; Svedholm-Häkkinen Anna-Mari; Lindeman Marjaana (Elsevier, 2022)
According to the Empathizing-Systemizing theory (E-S Theory), individual differences in how people understand the physical world (systemizing) and the social world (empathizing), are two continuums in the general population with several implications, from vocational interests to skills in the social and physical domains. The underlying mechanisms of intuitive physics performance among individuals with strong systemizing and weak empathizing (systemizers) are, however, unknown. Our results affirm higher intuitive physics skills in healthy adult systemizers (N=36), and further reveal the brain mechanisms that are characteristic for those individuals in carrying out such tasks. When the participants performed intuitive physics tasks during functional magnetic resonance imaging, combined higher systemizing and lower empathizing was associated with stronger activations in parts of the default mode network (DMN, cuneus and posterior cingulate gyrus), middle occipital gyrus, and parahippocampal region. The posterior cingulate gyrus and parahippocampal gyrus were specifically associated with systemizing “brain type” even after controlling for task performance, while especially in the parietal cortex, the activation changes were simply explained by higher task performance. We therefore suggest that utilization of DMN-parahippocampal complex, suggested to play a role in internalizing and activating long-term spatial memory representations, is the factor that distinguishes systemizers from empathizers with the opposite “brain type” in intuitive physics tasks.